Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 5 - Logarithmic, Exponential, and Other Transcendental Functions - 5.5 Exercises - Page 362: 59


$y=(-2 \ln 2)x-2 (\ln2 -1)$

Work Step by Step

$y=2^{-x}$ $y’=-\ln 2 (2^{-x})$ $y’(2) = \ln 2 (2^{-(-1)})$ $=-2 \ln 2$ $=14$ Equation of tangent: $y-2=-2 \ln 2(x+1)$ $y=(-2 \ln 2)x-2 (\ln2 -1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.